The Effect of Service Quality, Personal Selling, and Complaint Handling on Customer Retention of Sharia Bank Customers with Customer Satisfaction as Intervening Variable - Endri Saprudin; Hasan Al-Banna (Bulletin of Islamic Economics, 2022)
Customer retention is an important element of any banking strategy in today's increasingly competitive environment. The purpose of this study is to examine and explain the effect of service quality, personal selling, and complaint handling on customer retention in Islamic bank customers in Indonesia with customer satisfaction as an intervening variable. The population of this study was Islamic bank customers in Indonesia with sampling using a purposive sampling technique, the number of samples used in this study was 107 respondents. The data analysis technique used is SEM-PLS using Warp PLS version 7.0 as a data processing tool. The results of this study indicate that service quality, personal selling, and complaint handling have a significant positive effect on customer satisfaction. Customer satisfaction itself has a significant positive effect on customer retention, while the three independent variables have no significant effect directly on customer retention. Different results when service quality, personal selling, and complaint handling have a significant positive effect on customer retention after being mediated by customer satisfaction variables.